(untitled) (Journal of history, 2019)
The current situation in the archival world, the legal basis for the functioning of archives, approaches to the theoretical understanding of the science of archives and archival documents, methodological norms of archival practice, the organization of security and the use of documentary heritage – all these issues are of serious scientific and practical interest. Disclose the basic principles that guide the modern archival service of China; show the organization of archiving; familiarize with the composition and content of the most important archives, with the activities of archives in the field of acquisition, description, preservation and use of documents is the purpose of the article. In disclosing the main principles of the archival science of this country, attention was focused on its relationship with historical science, on the one hand, and documentation, on the other; on studying the experience of using the latest technical tools in archiving. The article introduces not only the experience of historical development and the current state of affairs in the field of archival affairs in China, but also helps to obtain a clear professional understanding of the need for knowledge and the possibility of comparing and applying foreign experience for domestic archival practice.